2021
DOI: 10.3390/microorganisms9102017
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation Ability of Arcobacter-like and Campylobacter Strains under Different Conditions and on Food Processing Materials

Abstract: Campylobacter jejuni is the most frequent cause of bacterial gastrointestinal food-borne infection worldwide. The transmission of Campylobacter and Arcobacter-like species is often made possible by their ability to adhere to various abiotic surfaces. This study is focused on monitoring the biofilm ability of 69 strains of Campylobacter spp. and lesser described species of the Arcobacteraceae family isolated from food, water, and clinical samples within the Czech Republic. Biofilm formation was monitored and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…In the literature, the biofilm formation ability of Arcobacter -like strains has been confirmed by many studies [ 32 , 33 , 34 ]. Biofilm activity differs among strains, and the environment also has a great influence on biofilm formation [ 35 ].…”
Section: Discussionmentioning
confidence: 89%
“…In the literature, the biofilm formation ability of Arcobacter -like strains has been confirmed by many studies [ 32 , 33 , 34 ]. Biofilm activity differs among strains, and the environment also has a great influence on biofilm formation [ 35 ].…”
Section: Discussionmentioning
confidence: 89%
“…The influence of the environment is not only fundamental to the planktonic cells of microorganisms, but also for biofilm formation [ 34 ]. In the literature, Arcobacter -like strains are generally described as weak biofilm producers [ 14 , 16 , 35 ]. However, our results show that some arcobacters are capable of intensive biofilm formation, even in the presence of antibiotics (e.g., Pseudarcobacter defluvii LMG 25694; see Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results show that some arcobacters are capable of intensive biofilm formation, even in the presence of antibiotics (e.g., Pseudarcobacter defluvii LMG 25694; see Figure 2 ). This fact could be explained by the higher biofilm formation in response to stress [ 16 ]. In contrast, many studies have shown that antibiotics at sub-MIC concentrations can significantly induce biofilm formation in a variety of bacterial strains in vitro [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations